MANFAAT INTERNET UNTUK IBU-IBU MASYARAKAT DUSUN KEDULAN TIRTOMARTANI KALASAN SLEMAN YOGYAKARTA - Harmastuti Harmastuti (LPPM IST AKPRIND Yogyakarta, 2020)
Internet is a network system connected globally around the world. The Internet can be used to communicate and provide information services quickly with many people, for organizing, businesses, government, education, banking or entrepreneurs. However, the internet also has positive and negative impacts. This paper writes about the implementation of community service activities about the benefits of the internet for women community at Dusun Kedulan Tirtomartani Kalasan Sleman Yogyakarta. Implementation begins with the introduction of the internet, its application and the practice of how to use it to support organizational activities, education, health, and home industry using phone cells and computers. The results obtained by the women community of Kedulan Tirtomartani Village, Kalasan, Sleman Yogyakarta, better understand the benefits of the Internet. As well as adding insights to organize, directing their children to use the internet, and being able to develop themselves, to be entrepreneurs from home online.